2011
DOI: 10.1007/s11914-011-0071-2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in the Persian Gulf: Integrative Physiology and Socioeconomic Factors

Abstract: Countries of the Persian Gulf region--Bahrain, Iran, Iraq, Kuwait, Oman, Qatar, Saudi Arabia, and United Arab Emirates--have become increasingly modernized, resulting in a transformation of lifestyle based on technology, sedentary activity, lack of sunlight, and unhealthy dietary patterns. These factors have led to a higher prevalence not only of vitamin D undernutrition, but also chronic obesity, insulin resistance, prediabetes, and type 2 diabetes. This review explores the integrative physiologic effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 56 publications
3
41
1
1
Order By: Relevance
“…Vitamin D deficiency was more pronounced among students with light brown complexion and employees with dark brown or black skin color. However, contrary to previous studies,25,27 the adjusted OR did not show significant impact of skin color on vitamin D deficiency. As it is difficult to assess the economic status using income categories, as the type of residence was used as an estimate for the economic class.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Vitamin D deficiency was more pronounced among students with light brown complexion and employees with dark brown or black skin color. However, contrary to previous studies,25,27 the adjusted OR did not show significant impact of skin color on vitamin D deficiency. As it is difficult to assess the economic status using income categories, as the type of residence was used as an estimate for the economic class.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite that some studies in the region did not find an association between clothing habits and vitamin D deficiency,23,24 others postulated that the conservative culture and concealed clothing style of females in the region were potential causes of low rates of sun exposure and high rates of vitamin D deficiency 13,25,26. Approximately two-thirds of students and employees had light brown skin color, approximately a third had white skin color, and very few had either dark brown or black skin color.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in Western countries have shown that vitamin D deficiency was present in 20% -25% of the total population [24]. In the Middle East region, approximately 60%–65% of the population was affected [1].…”
Section: Introductionmentioning
confidence: 99%
“…The deficiency is almost similar to those living in high latitudes countries (Binkley et al 2007;Lips 2007;Elsammak et al 2011). There is growing tendency for indoor activities by people living in these countries and this partly explains these findings (Fields et al 2011). Moreover, since the 1980's the public has been warned against sunlight exposure to reduce the risk of developing skin cancer and this has played a contributory role in high VDD (Ness et al 1999).…”
Section: What Is Vitamin D?mentioning
confidence: 99%